AlCl3 exposure induces nephrotoxicity in mice by mediating ferroptosis through the NRF2 signaling pathway - Liang, Liu-Dan; Zhao, Xiao-Yue; Li, Li; Liang, Sheng; Zhang, Jin-Min; Lv, Jian-Nan; Deng, Feng-Lian; Lu, Chun-Lei; Li, Qian; Huang, Qi-Wen; Huang, Mei-Jin; Peng, Hui-Xin (Frontiers in Toxicology, 2025)
Aluminum is toxic to both humans and animals. Exposure to AlCl3 can lead to kidney function damage, yet the specific underlying mechanism remains elusive. This study aimed to investigate whether ferroptosis is involved in the renal toxicity induced by AlCl3 exposure in mice and to elucidate its potential molecular mechanism. Forty-eight C57BL mice were randomly assigned to six groups, with eight mice in each group: a control group, low -, medium -, and high - dose aluminum exposure groups, a ferroptosis inhibitor group, and a ferroptosis inhibitor + high - dose aluminum exposure group. Mice in the aluminum exposure groups received intraperitoneal injections of different doses of AlCl3 solution for 4 weeks (5 times per week), while the ferroptosis inhibitor group was intraperitoneally injected with Fer - 1 for 4 weeks (2 times per week). After the experimental period, multiple indicators were examined. The results demonstrated that AlCl3 exposure impaired the renal function and structure of mice. It also led to an increase in lipid peroxidation products, Fe2+, and Al content in renal tissue. Moreover, the expression levels of genes and proteins such as GPX4 and Nrf2 were decreased, whereas the expression levels of the ACSL4 gene and protein were increased.However, after pretreatment with Fer - 1, the aforementioned indicators were ameliorated. Specifically, the expression of ACSL4 decreased, and the expression of GPX4 and other related factors increased.In conclusion, this study suggests that AlCl3 exposure may trigger ferroptosis in renal tissue cells by inhibiting the NRF2 pathway, thereby causing kidney function damage in mice. These findings provide a novel perspective on the mechanism of AlCl3 - induced renal toxicity.